The Role of Grammarly in Assessing English as a Foreign Language (EFL) Writing - Muhammad Ali Ghufron; Fathia Rosyida (Bina Nusantara University, 2018)
This research aimed at investigating the use of Grammarly software and in what terms it was more effective in reducing students’ errors in EFL writing compared to teacher corrective feedback (indirect corrective feedback). This research used the quantitative approach with a quasi-experimental design. There were 40 university students from English Education Study Program of a private university in Indonesia who were selected and randomized clustered into two; experimental and control groups. The students were tested at the beginning and the end of the research. The quantitative data were analyzed by using t-test formula. The results of the research confirm that the students whose work is evaluated by using Grammarly have a significant reduction in their errors compared to those whose work is evaluated by the teacher (indirect corrective feedback). The software is shown to be more effective to reduce the errors in terms of vocabulary usages (diction), language use (grammar), and mechanics of writing (spelling and punctuation). However, it is less effective to improve the content and organization of students’ EFL writing. This research can suggest EFL/ESL teachers with an alternative assessment for students’ writing that supports an autonomous learning environment.